PENGINTEGRASIAN SAINS KESIHATAN DALAM PENDIDIKAN ISLAM KSSM TINGKATAN SATU: KAJIAN KUASI-EKSPERIMEN: Integrated of Health Sciences into Islamic Education in Form One KSSM: A Quasi-Experimental Study - Mohammad Ghulam, Mohammad Syukor; Tengku Kasim, Tengku Sarina Aini; Abdul Kadir, Fakhrul Adabi (Journal of Islamic Educational Research, 2019)
Integrated of Health Sciences in Islamic Education is the teaching and learning approach by combining human health science into Islamic Study subject. The aim of this study is to identify the effectiveness of Integrated of Health Sciences into Islamic Education in Form One KSSM. This study is a Quantitative study and using the Quasi-Experimental design. The location of the study is one of the national high schools in Sungai Besi, Kuala Lumpur. The sampling method in the study is Purposive Sampling. A total of 50 students were chosen as the sample of the study, 25 of them as Control groups, while the remaining 25 students as Experimental groups. Method of collecting data is a test that is conducted twice as pre test and post test. The instrument of study is the topical test used in the PT3 exam format. The t-test of the Independent Sample in the Pre test showed that there was no significant mean difference between the Control group and the Experiment group with p = 0.105 (p> 0.05). While, in the post-test, the t-test of the Independent Sample shows that the value of p = 0.000 (p <0.05) with the mean score for the Experiment group was higher (66.24) compared with the control group min score (51.80) and the difference was significant. This indicates the intervention has affected the increase in the mean score of the Experiment group.